Digital Citizenship to Prevent Cyberbullying Behaviour - Yuniawati , Elisa Ika; Beng , Jap Tji; Tiatri , Sri (Jurnal Pengabdian Kepada Masyarakat Untukmu Nusantara, 2025)
The internet as an information and communication technology product has positive and negative impacts. One of the negative impacts is the emergence of negative online behavior such as cyberbullying which has an impact on mental health which affects the welfare of life and disrupts individual cognition. In Indonesia itself, throughout 2020, 45% of Indonesian children aged 14-24 and 20% aged 13-17 were victims of cyberbullying either at school, home, or the surrounding environment. Based on the results of a survey and also discussions with teachers and junior high school students in one of the regencies of Bali, several students had received harsh words and negative comments through social media which are indicators of negative cyberbullying behavior. Therefore, efforts are needed through the introduction and implementation of special programs as prevention as an effective intervention in reducing cyberbullying behavior. One effort that can be made is through the application of digital citizenship such as ethical behavior in the digital world to prevent individuals from exposing inappropriate behavior in technology. The implementation method is through psychoeducation in schools for students and teachers which is packaged with lectures, games, and interactive questions and answers. It is expected that this activity can increase students’ knowledge about the description of the types of negative online cyberbullying behavior that occurs between students, especially in junior high school environments, and provide schools with a description of digital citizenship behavior so that it can be a consideration for schools in making policies and changing behavior to be better and creating a school environment that is free from negative online cyberbullying behavior. The outputs of this study are: 1) Implementation of digital citizenship behavior to reduce cyberbullying behavior, 2) the results of this activity in the form of posters as a campaign to prevent cyberbullying through digital citizenship